KEARIFAN LOKAL MASYARAKAT ADAT CEREKANG DALAM MENJAGA DAN MELESTARIKAN HUTAN ADAT DI DESA MANURUNG - Maria Maria; Taskur Taskur; Hadijah azis Karim (Jurnal Penelitian Kehutanan BONITA, 2020)
Indigenous people have the knowledge from generation to generation to maintain and protect forest resources around them. The role of local wisdom of the Cerekang indigenous people in protecting and preserving the customary forest is very much needed for the survival and function of the forest. This study aims to describe and explain the role of local wisdom of indigenous peoples in protecting and preserving customary forests. Data obtained directly through surveys and direct field observations, data collected through observation and interview methods are processed and classified according to research objectives and then analyzed using qualitative data analysis. The results obtained are that the Cerekang customary forest is a customary forest that has a principle of sustainability, there is no management at all by the cerekang customary community so that in maintaining and preserving the cerekang customary forest it is carried out by customary stakeholders, customary institutions, Cerekang customary communities and the village government